536 Use of A Cost-Efficient Colonoscopy Simulation Model to Improve Endoscopy Skills During the COVID Pandemic. (4th May 2021) - MacDonald, S; Edgar, B; Stokes, E; McDade, D; Anderson, J; Macdonald, A
Abstract: Introduction: The use of endoscopic simulators as a learning aid in surgical training has been well established. This has been emphasised during the challenging times of COVID-19. However, their utility for training is countered by the high cost of the equipment, with the most basic simulators costing upwards of £50, 000. Method: A simple polypectomy simulator model was created using a drain-pipe and surgical gloves. n = 9 junior doctors were timed in their ability to remove the 3 polyps from the simulator. The exercise was repeated over 6 sessions over the course of 3 weeks. Means were compared using ANOVA. Results: There was a mean relative reduction of 75% in overall time taken to complete the task(p < 0.0001). This improvement was seen for both surgical trainees(p = 0.005) and FY1 novices(p < 0.0001) and junior doctors reported feeling more confident with basic Colonoscopic skills. Conclusions: We have demonstrated an improvement in performance times across both surgical trainees and novices. In today's era of COVID-19, when direct training opportunities may become more scarce, simple alternatives may become vital in ensuring progression of basic surgical skills such as endoscopy. This cheap polypectomy simulator can be easily re-created across surgical units and can be used as an adjunct to traditional endoscopic training